Analisis Strategi Pemasaran Kampung Wisata Rajut Binong Jati Dalam Penjualan Produk Rajut - Nalya Arum Fathanah; Muhammad Zaki Fadhilan Burhanudin (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This study aims to analyze and find out the marketing strategy in Binong Jati Knitting Tourism Village in selling knitting products. The problem in this study is that the marketing strategy implemented by Binong Jati Knitting Tourism Village for the sale of knitting products has not been maximized and has not had a positive impact on Binong Jati Knitting Tourism Village. Marketing strategy is a planned way and structure to attract consumers. The marketing strategy includes steps that will be taken to promote, distribute, and sell the product or service. The marketing strategy that can be applied to Binong Jati Knitting Tourism Village in selling knitting products from the analysis that has been done is to increase attractive promotions for knitting products in the Binong Jati Knitting Tourism Village Area. Secondary data sources are used in this research, which uses descriptive qualitative research methodology. The results of this study discuss the important role of marketing strategies that must be applied in Binong Jati Knitting Tourism Village to increase sales of knitting and the Binong Jati Knitting industry so that it can be recognized by more domestic or foreign tourists.